Law of the republic of Indonesia number 5 of 1992 : concerning items of cultural proparty - Indonesia. Departement of Education and Culture of the Republic of Indonesia (Departement of Education and Culture of the Republik of Indonesia, 1996)
i, 33 p.; 18 cm.